2018
DOI: 10.3390/su10051613
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Improved Air Quality and Influencing Factors among Manufacturing Workers in Nanchang, China

Abstract: (1) Background: Air quality apt to deteriorate in decades in China, people are seeking improvement measures. To assess the willingness to pay (WTP) for improved air quality among manufacturing workers and associated factors influencing their WTP. (2) Methods: A cross-sectional questionnaire survey was conducted in combination with contingent valuation in Nanchang between September and October of 2015. A face-to-face interview was conducted to obtain basic demographic information from manufacturing workers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
4
15
0
Order By: Relevance
“…Respondents believes that there was a need to involve all stakeholders such as family and friends, the media, environmental organisations, tertiary institutions and researchers. This is in line with other studies, which have emphasised the need for a collective effort in improving the air quality in the city [30].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Respondents believes that there was a need to involve all stakeholders such as family and friends, the media, environmental organisations, tertiary institutions and researchers. This is in line with other studies, which have emphasised the need for a collective effort in improving the air quality in the city [30].…”
Section: Discussionsupporting
confidence: 92%
“…This study found that there was a statistical significant association between the knowledge, behaviour, and attitudes regarding air pollution (P-values >0.05). Increased air pollution awareness among community members can lead to early acceptance of air pollution policies, and interventions as well as a willingness to take protective measures [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…However, Birdir et al [65] reported 92% WTP amount to see the improved beaches in Mersin, Turkey. Liu et al [98] reported the 53% rate of WTP for improved air quality in China. In New Zealand, Omwenga [99] reported 25.8% in CV case studies.…”
Section: Characteristics Of the Respondentsmentioning
confidence: 99%
“…This study findings indicated high rate of WTP as compared to other previous studies. For instance, Liu et al [51] reported 53% rate of WTP for improved air quality in China. In New Zealand, Omwenga, [52] reported 25.8% in CV case studies.…”
Section: Discussionmentioning
confidence: 99%